Diversity, toxicity, and distribution of potentially toxic diatoms in Antarctic waters––With description of Pseudo-nitzschia meridionalis sp. nov. and P. glacialis sp. nov. - Lundholm, Nina; Christensen, Anneliese L.; Olesen, Anna K.J.; Beszteri, Bánk; Eggers, Sarah Lena; Krock, Bernd; Altenburger, Andreas (Harmful Algae, 2024)
Diatoms of the genus Pseudo-nitzschia, known for their potential toxicity, are integral to the phytoplankton community of the Southern Ocean, which surrounds Antarctica. Despite their ecological importance, the diversity and toxicity of Pseudo-nitzschia in this region remain underexplored. Globally, these diatoms are notorious for forming harmful algal blooms in temperate and tropical waters, causing significant impacts on marine life, ecosystems, and coastal economies. However, detailed information on the diversity, morphology, and toxicity of Pseudo-nitzschia species in Antarctic waters is limited, with molecular characterizations of these species being particularly scarce. During three research expeditions to the Southern Ocean, monoclonal strains of Pseudo-nitzschia were isolated and cultivated. Stored samples from a fourth expedition, the Brategg expedition, were used to complete the description of particularly P. turgidula. Through electron microscopy and molecular analysis, two novel species were identified—Pseudo-nitzschia meridionalis sp. nov. and Pseudo-nitzschia glacialis sp. nov.—alongside the previously described species P. subcurvata, P. turgiduloides, and P. turgidula. Toxin assays revealed no detectable levels of domoic acid in P. turgiduloides, P. turgidula, P. meridionalis sp. nov. and P. glacialis sp. nov. Conversely, P. subcurvata was reported in a related study to produce domoic acid and its isomer, isodomoic acid C. These findings emphasize the need for comprehensive research on the phytoplankton of Antarctic waters, which is currently a largely uncharted domain. With the looming threat of climate change, understanding the dynamics of potentially harmful algal populations in this region is becoming increasingly critical.
Article Number: 102724
Keywords: Rosshavet; Sørishavet; alger; biodiversitet; diatomeer; fytoplankton; marin biologi

The Late Holocene deglaciation of James Ross Island, Antarctic Peninsula: OSL and 14C-dated multi-proxy sedimentary record from Monolith Lake - Roman, Matěj; Píšková, Anna; Sanderson, David C.W.; Cresswell, Alan J.; Bulínová, Marie; Pokorný, Matěj; Kavan, Jan; Jennings, Stephen J.A.; Lirio, Juan M.; Nedbalová, Linda; Sacherová, Veronika; Kopalová, Kateřina; et al. (Quaternary Science Reviews, 2024)
Lentic waterbodies provide terrestrial sedimentary archives of palaeoenvironmental change in deglaciated areas of the Antarctic. Knowledge of the long-term evolution of Antarctic palaeoenvironments affords important context to the current marked impacts of climate change in the Polar regions. Here, we present a comprehensively dated, multi-proxy sedimentary record from Monolith Lake, a distal proglacial lake in one of the largest ice-free areas of the Antarctic Peninsula region. Of the two defined sedimentary units in the cores studied, the lower Unit 1 exhibits a homogeneous composition and unvarying proxy data profiles, suggesting rapid clastic deposition under uniform, ice-proximal conditions with a sedimentation rate of ∼1 mm yr−1. 14C and optically stimulated luminescence (OSL) dating bracket the deposition interval to 1.5–2.5 ka BP, with the older age being more probable when compared to independent dating of the local deglaciation. The uppermost 11 cm of the record spans the last ∼2.2 ka BP (maximum age), suggesting a markedly decreased sedimentation rate of ∼0.05 mm yr−1 within Unit 2. Whereas Unit 1 shows only scarce evidence of biological activity, Unit 2 provides an uninterrupted record of diatoms (with 29 species recorded) and faunal subfossils, including the fairy shrimp Branchinecta gaini. Concentrations of organically-derived elements, as well as diatoms and faunal remains, are consistent, implying a gradual increase in lake productivity. These results provide an example of long-term Antarctic ‘greening’ (i.e. increasing organic productivity in terrestrial habitats) from a palaeolimnological perspective. The boundary between Units 1 and 2, therefore, marks the timing of local deglaciation at the final stages of a period of negative glacier mass balance, i.e. the Mid-Late Holocene Hypsithermal. Subsequent Neoglacial cooling is evidenced by the abated influence of glacial meltwater streams and turbidity decline linked to reduced glacier runoff, although most proxy responses mirror the natural proglacial lake ontogeny.
Keywords: Antarktis; diatomeer; geografi; geologi; holocene; innsjøer; paleolimnologi; paleoøkologi

Tintinnid ciliates of Amundsen Sea (Antarctica) plankton communities - Dolan, John R; Yang, Eun Jin; Lee, Sang Hoon; Kim, Sun Young (Polar Research, 2013)
The Amundsen Sea has been described as one of the most productive and dynamic pelagic systems in Antarctica and is one of the least studied. Based on samples from 15 stations in the Amundsen Sea, we describe for the first time the composition of the tintinnid ciliate assemblage of the microzooplankton. We compared the species compositions of coastal polynya sites, where the phytoplankton communities are dominated by Phaeocystis, to those of the offshore deep water sites, which are dominated by diatoms. We found a total of 15 species. Polynya sites were dominated by a few species of tintinnids, mostly those endemic to the Southern Ocean. In contrast, the deep-water sites contained many widespread tintinnid species, which are known from a wide variety of systems as well as other areas of the Southern Ocean. We examined polymorphism known to characterize the Antarctic tintinnid species Cymatocylis affinis/convallaria and Codonellopsis gaussi. We found that the types or forms found appeared unrelated to the type of microplankton community, defined by the identity of the dominant phytoplankton taxa. However, the number of different morphotypes found at a site appeared related to the overall concentration of the species, suggesting that different morphologies, previously considered distinct species, may simply be developmental stages. Keywords: Zooplankton; microzooplankton; polynya; protists; Phaeocystis; diatoms.
Keywords: Sørishavet; diatomeer; fytoplankton; marin biologi; oseanografi; protoktister; zooplankton; økologi

Inorganic C utilization and C isotope fractionation by pelagic and sea ice algal assemblages along the Antarctic continental shelf - Tortell, Philippe D; Mills, Mathew M; Payne, Christopher D; Maldonado, Maria T; Chierici, Melissa; Fransson, Agneta; Alderkamp, Anne-Carlijn; Arrigo, Kevin R (Marine Ecology Progress Series, 2013)
Physiological characteristics of inorganic C uptake were examined in Southern Ocean ice algae and phytoplankton assemblages. Ice algal and phytoplankton assemblages were largely dominated by diatoms and Phaeocystis antarctica, and showed a high capacity for HCO3- utilization, with direct HCO3- transport accounting for ~60% of total inorganic C uptake. Extracellular carbonic anhydrase (eCA) was detectable in all samples, but with significantly lower activity in sea ice algae. Neither HCO3- transport nor eCA activity was related to the in situ partial pressure of CO2 (pCO2) or taxonomic composition of samples. The half-saturation constant (KS) for inorganic C ranged from ~100 to 5000 µM, and showed significantly more variability among sea ice algae than phytoplankton assemblages. For the phytoplankton assemblages, there were significant positive correlations between in situ pCO2 and KS (higher C substrate affinity in low pCO2 waters), and also between KS and maximum C uptake rates (Vmax). In contrast, KS and Vmax in sea-ice algal assemblages were not correlated to each other, or to any other measured variables. The C isotope composition of particulate organic carbon(δ13C-POC) in the phytoplankton assemblages showed modest variability (range -30 to -24.6‰) and was significantly correlated to the ratio of inferred growth rates (derived from Vmax) and in situ CO2 concentrations, but not to any measured C uptake parameters. δ13C-POC in sea ice algal samples (range -25.7 to -12.9‰) was significantly heavier than in the phytoplankton assemblages, and not correlated to any other variables. Our results provide evidence for the widespread occurrence of carbon-concentrating mechanisms in Southern Ocean sea ice algae and phytoplankton assemblages. KEYWORDS: Phytoplankton · Sea ice algae · Inorganic carbon uptake · HCO3- · Carbonic anhydrase
Keywords: Sørishavet; alger; biokjemi; diatomeer; fytoplankton; kjemiske analyser; kontinentalsokkel; marin biologi

Neogene biochronology of Antarctic diatoms: A comparison between two quantitative approaches, CONOP and UAgraph - Galster, Federico; Guex, Jean; Hammer, Oyvind (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
A quantitative biochronological study by Cody et al. (2008) integrates comprehensive diatom biostratigraphy, magnetostratigraphy, and tephrostratigraphy from 32 Neogene sections around the Southern Ocean and Antarctic continental margin. A recent method, known as Constrained Optimization (CONOP), which can be viewed as a multidimensional version of graphic correlation, is applied to that very interesting database. The goal of the present paper is to discuss some theoretical aspects of quantitative biochronology and to compare the constrained optimization with the deterministic method called Unitary Associations (UAM), a graph theoretical model. We illustrate the fact that the UAM is an extremely powerful and unique theory allowing an in-depth analysis of the internal conflicting inter-taxon stratigraphic relationships, inherent to any complex biostratigraphical database.
Keywords: Antarktis; Sørishavet; biokronologi; diatomeer; paleogeografi; paleoklimatologi; paleontologi; paleoøkologi

Observations on the relationship between the Antarctic coastal diatoms Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen and sea ice concentrations during the late Quaternary - Pike, Jennifer; Crosta, Xavier; Maddison, Eleanor J.; Stickley, Catherine E.; Denis, Delphine; Barbara, Loïc; Renssen, Hans (Marine Micropaleontology, 2009)
The available ecological and palaeoecological information for two sea ice-related marine diatoms (Bacillariophyceae), Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen, suggests that these two species have similar sea surface temperature (SST), sea surface salinity (SSS) and sea ice proximity preferences. From phytoplankton observations, both are described as summer or autumn bloom species, commonly found in low SST waters associated with sea ice, although rarely within the ice. Both species form resting spores (RS) as irradiance decreases, SST falls and SSS increases in response to freezing ice in autumn. Recent work analysing late Quaternary seasonally laminated diatom ooze from coastal Antarctic sites has revealed that sub-laminae dominated either by T. antarctica RS, or by P. glacialis RS, are nearly always deposited as the last sediment increment of the year, interpreted as representing autumn flux. In this study, we focus on sites from the East Antarctic margin and show that there is a spatial and temporal separation in whether T. antarctica RS or P. glacialis RS form the autumnal sub-laminae. For instance, in deglacial sediments from the Mertz Ninnis Trough (George V Coast) P. glacialis RS form the sub-laminae whereas in similar age sediments from Iceberg Alley (Mac.Robertson Shelf) T. antarctica RS dominate the autumn sub-lamina. In the Dumont d'Urville Trough (Adélie Land), mid-Holocene (Hypsithermal warm period) autumnal sub-laminae are dominated by T. antarctica RS whereas late Holocene (Neoglacial cool period) sub-laminae are dominated by P. glacialis RS. These observations from late Quaternary seasonally laminated sediments would appear to indicate that P. glacialis prefers slightly cooler ocean–climate conditions than T. antarctica. We test this relationship against two down-core Holocene quantitative diatom abundance records from Dumont d'Urville Trough and Svenner Channel (Princess Elizabeth Land) and compare the results with SST and sea ice concentration results of an Antarctic and Southern Ocean Holocene climate simulation that used a coupled atmosphere–sea ice–vegation model forced with orbital parameters and greenhouse gas concentrations. We find that abundance of P. glacialis RS is favoured by higher winter and spring sea ice concentrations and that a climatically-sensitive threshold exists between the abundance of P. glacialis RS and T. antarctica RS in the sediments. An increase to >0.1 for the ratio of P. glacialis RS:T. antarctica RS indicates a change to increased winter sea ice concentration (to >80% concentration), cooler spring seasons with increased sea ice, slightly warmer autumn seasons with less sea ice and a change from ~7.5months annual sea ice cover at a site to much greater than 7.5months. In the East Antarctic sediment record, an increase in the ratio from <0.1 to above 0.1 occurs at the transition from the warmer Hypsithermal climate into the cooler Neoglacial climate (~4cal kyr) indicating that the ratio between these two diatoms has the potential to be used as a semi-quantitative climate proxy.
Keywords: Sørishavet; Weddellhavet; diatomeer; havis; marin biologi; mikropaleontologi; paleontologi; paleoøkologi; sjøis

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

Comparison of contemporary and fossil diatom assemblages from the western Antarctic Peninsula shelf - Pike, Jennifer; Allen, Claire S.; Leventer, Amy; Stickley, Catherine E.; Pudsey, Carol J. (Marine Micropaleontology, 2008)
During the past ten years, the Antarctic Peninsula has been identified as the most rapidly warming region of the Southern Hemisphere and it is important to place this warming in the context of the natural climate and oceanographic variability of the recent geological past. Many biological proxies, such as marine diatom assemblages, have been used to determine Southern Ocean palaeoceanographic conditions during the Late Quaternary, however, few investigations have attempted to link observations of modern floras with the fossil record. In this study we examine a suite of modern austral spring (December 2003) and summer (February 2002) surface water samples from along the western Antarctic Peninsula (WAP) continental shelf and compare these to core-top, surface sediment samples. Using detrended correspondence analysis (DCA) and principal component analysis (PCA) of diatom abundance data we investigate the relationship of contemporary diatom floras with the fossil record. This multivariate analysis reveals that our modern assemblages can be divided into three groups: summer southern WAP sites, summer northern WAP sites, and spring WAP sites. Sea surface temperature (SST) is an important environmental variable for explaining seasonal differences in diatom assemblages between spring and summer, but sea surface salinity (SSS) is more important for understanding temporally-equivalent regional variations in assemblage. Our summer diatom samples are more reminiscent of early season assemblages, reflecting the unusually late sea ice retreat from the region that year. When the modern assemblages are compared to the fossil record, it is clear that most of the important diatoms from the summer assemblage are not preserved into the sediments, and that the fossil record more closely reflects spring assemblages. This observation is important for any future attempts to quantitatively reconstruct palaeoceanographic conditions along the WAP during the Late Quaternary and highlights the need for many more such studies in order to address longer timescales, such as interannual variability, in the context of the fossil record.
Keywords: Sørishavet; Vestantarktis; diatomeer; marin biologi; marin geologi; mikropaleontologi; paleoseanografi

The diatom Fragilariopsis cylindrus and its potential as an indicator species for cold water rather than for sea ice - Quillfeldt von, Cecilie Hellum (Vie et Milieu / Life & Environment, 2004)
The importance of the diatom Fragilariopsis cylindrus (Grunow) Krieger in Helmcke & Krieger in the Arctic and Antarctic is well known. It is used as an indicator of sea ice when the paleoenvironment is being described. It is often among the dominant taxa in different sea ice communities, sometimes making an important contribution to a subsequent phytoplankton growth when released by ice melt. However, it may also dominate phytoplankton blooms in areas never experiencing sea ice. The use of F. cylindrus as an indicator for reconstruction of palaeoceanographic conditions is assessed from literature records. Its potential as an indicator species for sea ice appears to vary from region to region, but it is a good indicator of cold water.
Keywords: Sørishavet; diatomeer; marin biologi; paleoseanografi; phytoplankton; polarområdene

Synedropsis gen. nov., a genus of araphid diatoms associated with sea ice - Hasle, Grethe Rytter; Medlin, Linda K.; Syvertsen, Erik E. (Phycologia, 1994)
A new araphid diatom genus, Synedropsis Hasle, Medlin et Syvertsen, is described from sea ice. The generitype, Synedropsis hyperborea (Grunow) Hasle, Medlin et Syvertsen from the Arctic, was first described as a species of Synedra, as was the antarctic Synedropsis fragilis (Manguin) Hasle, Syvertsen et Medlin. A second antarctic species of Synedropsis is a new combination of Cymatosira laevis Heiden in Heiden & Kolbe. In addition four new taxa, S. hyperboreoides Hasle, Syvertsen et Medlin, S. recta Hasle, Medlin et Syvertsen, S. lata Hasle, Medlin et Syvertsen and S. lata var. angustata Hasle, Medlin et Syvertsen are described from the Antarctic. The valve wall is laminar with uniseriate, often poorly developed striae and a wide sternum. Each valve possesses apical fields composed of slits. A labiate process is positioned near one apical slit field. The valve outline for most species exhibits considerable stadial variation. The girdle has several bands, most with one row of poroids close to the pars interior. Thus Synedropsis is closely related to the marine Fragilaria striatula Lyngbye except in the structure of the apical fields and the number of bands. Species observed in uncleaned material appeared in stellate or, more seldom, ribbon-shaped colonies. Synedropsis hyperborea is a common epiphyte on the ice-associated Melosira arctica Dickie in the Arctic. The antarctic species were found mainly in the bottom ice community, S. fragilis as an epiphyte on other diatoms.
Publisher: Taylor & Francis
Keywords: Rosshavet; Sørishavet; Weddellhavet; botanikk; diatomeer; havis; kiselalger; marin biologi; plankton

Phytoplankton distribution in relation to sea ice, hydrography and nutrients in the northwestern Weddell Sea in early spring 1988 during EPOS - Bianchi, Franco; Boldrin, Alfredo; Cioce, F; Dieckmann, Gerhard Stephan; Kuosa, Harri; Larsson, A M; Nöthig, Eva-Maria; Sehlstedt, P I; Socal, Giorgio; Syvertsen, Erik E (Polar Biology, 1992)
Phytoplankton biomass and distribution of major phytoplankton groups were investigated in relation to sea ice conditions, hydrography and nutrients along three north-south transects in the north western Weddell Sea in early spring 1988 during the EPOS Study (European Polarstern Study), Leg 1. Three different zones along the transects could be distinguished: 1) the Open Water Zone (OWZ) from 58-degrees to 60-degrees-S with high chlorophyll a concentrations up to 3.5-mu-g l-1; 2) the Marginal Ice Zone (MIZ) from 60-degrees to about 62.5-degrees with chlorophyll a concentrations between 0.1 and 0.3-mu-g l-1, and 3) the closed pack-ice zone (CPI) from 62.5-degrees to 63.2-degrees-S with chlorophyll a concentrations below 0.1-mu-g l-1. Nutrient concentrations increased towards the south showing winter values under the closed pack-ice. Centric diatoms such as Thalassiosira gravida and Chaetoceros neglectum forming large colonies dominated the phytoplankton assemblage in terms of biomass in open water together with large, long chain forming, pennate diatoms, whereas small pennate diatoms such as Nitzschia spp., and nanoflagellates prevailed in ice covered areas. Fairly low concentrations of phytoplankton cells were encountered at the southernmost stations and many empty diatom frustules were found in the samples. The enhanced phytoplankton biomass in the Weddell-Scotia-Confluence area is achieved through sea ice melting in the frontal zone of two different water masses, the Weddell and the Scotia Sea surface waters.
Keywords: Sørishavet; Weddellhavet; biomasse; diatomeer; fytoplankton; havis; hydrografi; marin biologi; oseanografi

Microbial communities from the sea ice and adjacent water column at the time of ice melting in the northwestern part of the Weddell Sea - Mathot, Sylvie; Becquevort, Sylvie; Lancelot, Christiane (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; alger; bakterier; diatomeer; havis; mikrobiologi; protozo; sjøis; smelting

Some Nitzschia and related diatom species from fast ice samples in the Arctic and Antarctic - Medlin, Linda K.; Hasle, Grethe Rytter (Polar Biology, 1990)
Some Nitzschia and closely related species have been examined in the light and electron microscopes from fast ice samples in the Arctic and Antarctic. Nitzschia neofrigida, forming arborescent colonies, and Nitzschia promare, forming loose ribbon colonies, are described as new species, both probably included in the distribution of other similar species. A new combination, Auricula compacta, represents the first report of this genus from ice samples. Colony formation is reported for the first time in Nitzschia arctica and Nitzschia taeniiformis. No biopolar species were found and several reports of Arctic species in Antarctic ice samples have been refuted.
Keywords: Antarktis; alger; biodiversitet; biologi; botanikk; diatomeer; fytoplankton; planteplankton; polarområdene

Resting spore formation in the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo - Syvertsen, Erik E. (Polar Biology, 1985)
The resting spore morphology of the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo are described. Both species form endogenous resting spores. The spore valve of C. furcatus differ from those of the vegetative cells primarily by (i) a greater convexity and (ii) a coarser and more distinctly fasciculated areolation. This resting spore is identical to the diatom traditionally identified as C. stellaris var. symbolophorus (Grunow) Jørgensen in the Antarctic. The resting spore of T. australis differs from the vegetative cells by (i) a lack of clusters of strutted processes in a modified ring on valve face, (ii) a coarser areolation and tangential rows of areolae and (iii) a narrower and more simply structured girdle. The resting spore valve of T. australis has been described as belonging to a separate species, Actinocyclus excentricus Peragallo.
Keywords: Sørishavet; diatomeer; marinbiologi

The antarctic diatoms Thalassiosira dichotomica (Kozlova) comb. nov. and T. ambigua kozlova - Fryxell, Greta A.; Hasle, Grethe Rytter (Polar Biology, 1983)
Two small antarctic diatoms, usually missed by traditional collection methods, have been studied in light and electron microscopes. Porosira dichotomica has been transferred to Thalassiosira since its valve structure and process pattern agree better with that genus. T. dichotomica is unusual in that some lines of areola walls are extended, sail-like, out from the valve, supporting Kozlova's original drawings. T. ambigua, the smaller of the two, has many similarities in structure with T. dichotomica, but has granules on the margin, lacks the sail-like structures on the valve, and has minor differences in processes and areola size. Bands stay together in T. ambigua and show more fine structure than many species in the genus.
Keywords: Sørishavet; diatomeer; marin biologi; oseanografi

The genus Thalassiosira: species with internal extensions of the strutted processes - Fryxell, Greta A; Hasle, Grethe Rytter (Phycologia, 1979)
Publisher: Taylor & Francis
Keywords: Sørishavet; diatomeer; marinbiologi; oseanografi

Diatoms: Cleaning and Mounting for Light and Electron Microscopy - Hasle, Grethe R; Fryxell, Greta A (Transactions of the American Microscopical Society, 1970)
Publisher: [American Microscopical Society, Wiley]
Keywords: Sørishavet; Weddellhavet; diatomeer; marinbiologi; oseanografi

Morphology and distribution of the marine centric diatom Thalassiosira antarctica Comber - Hasle, Grethe R; Heimdal, Berit R (Journal of the Royal Microscopical Society, 1968)
Keywords: Sørishavet; diatomeer; fytoplankton; marinbiologi; plankton